Optimizing Tourism Offers with COPRAS-SVNS for Stress Reduction and Sustainability Promotion - Freddy Anaximandro Álvarez Lema; Manuel Antonio Abarca Zaquinaula; Milton Alberto Sampedro Arrieta; Rodolfo Matius Mendoza Poma (Neutrosophic Sets and Systems)
This study focused on the evaluation of tourist packages in the Pichincha region, Ecuador, designed to combine sustainability and stress reduction. Its main objective was to identify the most effective alternatives using multicriteria decision methods, incorporating neutrosophic logic as a key approach. Eight tourist packages were analyzed, integrating activities such as reforestation, meditation, and rural tourism with organic gardens, all aimed at environmental sustainability and the emotional well-being of participants. Using the neutrosophic correlation method, the most relevant criteria for subsequent analysis were selected. The application of the COPRAS-SVNS method determined that the "Eco-destinations with electric bicycle" package represented the best option, as it optimally balanced the objectives of sustainability and stress reduction. The study emphasized the relevance of neutrosophic logic in addressing the uncertainty and ambiguity inherent in evaluating complex tourist alternatives.